Aloe-derived vesicles enable macrophage reprogramming to regulate the inflammatory immune environment - Zhou, Hao; Peng, Ke; Wang, Jun; Wang, Yang; Wang, Jia-Jia; Sun, Shi-Kun; Shi, Mai-Qing; Chen, Jun; Ji, Fu-Hai; Wang, Xu (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Bacterial pneumonia poses a significant global public health challenge, where unaddressed pathogens and inflammation can exacerbate acute lung injury and prompt cytokine storms, increasing mortality rates. Alveolar macrophages are pivotal in preserving lung equilibrium. Excessive inflammation can trigger necrosis in these cells, disrupting the delicate interplay between inflammation and tissue repair. Methods: We obtained extracellular vesicle from aloe and tested the biosafety by cell viability and hemolysis assays. Confocal microscopy and flow cytometry were used to detect the uptake and internalization of extracellular vesicle by macrophages and the ability of extracellular vesicle to affect the phenotypic reprogramming of macrophages in vitro. Finally, we conducted a clinical feasibility study employing clinical bronchoalveolar lavage fluid as a representative model to assess the effective repolarization of macrophages influenced by extracellular vesicle. Results: In our study, we discovered the potential of extracellular vesicle nanovesicles derived from aloe in reprograming macrophage phenotypes. Pro-inflammatory macrophages undergo a transition toward an anti-inflammatory immune phenotype through phagocytosing and internalizing these aloe vera-derived extracellular vesicle nanovesicles. This transition results in the release of anti-inflammatory IL-10, effectively curbing inflammation and fostering lung tissue repair. Discussion: These findings firmly establish the immunomodulatory impact of aloe-derived extracellular vesicle nanovesicles on macrophages, proposing their potential as a therapeutic strategy to modulate macrophage immunity in bacterial pneumonia.